2010
DOI: 10.1002/sia.3348
|View full text |Cite
|
Sign up to set email alerts
|

Surface investigation of carbon films: from diamond to graphite

Abstract: In the present work, a detailed spectroscopic investigation of carbon in different crystalline forms from diamond to graphite was carried out. The spectra of photoemission peak, plasmon losses and X-rays-excited C KLL were studied in order to characterize the carbon phase in different samples. In addition, a method for determination of sp 2 /sp 3 ratio from the first derivative of Auger C KLL spectrum was employed. The obtained results indicated that carbon photoemission peak for sp 2 and sp 3 configurations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 18 publications
9
142
0
Order By: Relevance
“…It is found that the D values obtained from the Tidoped diamond layers are very far from those of graphite (ranging between 21.0 and 22.5 eV), diamondlike carbon or hydrogenated amorphous carbon (ranging between 15 and 20 eV). In particular, for D3, D4, and D5 films, D values of 14.5 ± 0.5, 14.0 ± 0.5, and 14.5 ± 0.5 are respectively detected, and prove to be in a very good agreement with the values 14.2 ± 0.5 and 13.7 ± 0.5 eV previously found for CVD diamond by Lascovich et al [24] and by Mezzi et al, [25] respectively. Moreover, it is to be noted that no signals deriving from other Ti including species are detected by the AES analysis.…”
Section: Auger Analysissupporting
confidence: 86%
“…It is found that the D values obtained from the Tidoped diamond layers are very far from those of graphite (ranging between 21.0 and 22.5 eV), diamondlike carbon or hydrogenated amorphous carbon (ranging between 15 and 20 eV). In particular, for D3, D4, and D5 films, D values of 14.5 ± 0.5, 14.0 ± 0.5, and 14.5 ± 0.5 are respectively detected, and prove to be in a very good agreement with the values 14.2 ± 0.5 and 13.7 ± 0.5 eV previously found for CVD diamond by Lascovich et al [24] and by Mezzi et al, [25] respectively. Moreover, it is to be noted that no signals deriving from other Ti including species are detected by the AES analysis.…”
Section: Auger Analysissupporting
confidence: 86%
“…[35,36] A primary peak was seen for C 1s for all samples at 284.5 eV corresponding to CC and CH species, followed by peaks at 286.0, 287.5, 289.2, and 290.9 eV for CO and CN, CO, carbonates, and π to π * transitions, respectively ( Figure S9, Supporting Information). [36,37] Adv. Mater The increase in π to π * after carbonization is likely due to the material becoming more graphitic in nature.…”
Section: Doi: 101002/adma201603051mentioning
confidence: 99%
“…This lack of knowledge inhibits developing a fundamental understanding of the mechanisms by which the excellent thermal stability and tribological performance of a-C:H:Si:O are achieved. To gain insights into the structure and composition of DLCs, some of the most powerful tools in the material characterization arsenal have been used, including Raman spectroscopy [9,[16][17][18][19], X-ray photoelectron spectroscopy (XPS) [13,20,21], near edge X-ray absorption fine structure (NEXAFS) spectroscopy [22][23][24], electron energy loss spectroscopy (EELS) [25], Fourier-transform infrared spectroscopy (FT-IR) [26], X-ray reflectivity (XRR) [25], forward recoil elastic scattering (FRES) [27], nuclear magnetic resonance (NMR) spectroscopy [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], and electron paramagnetic resonance (EPR) spectroscopy [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%